Marx’s Scientific Practice View from the Outline of Feuerbach - Ding, Honghong (International Journal of Social Sciences and Public Administration, 2024)
Marx, in his "Theses on Feuerbach" (hereinafter referred to as the "Theses"), starts from practice and reveals and criticizes the main flaws of previous philosophy: old materialism cannot see that the sensory world is a product of human practical activities; Idealism understands practice as abstract spiritual labor and exaggerates human subjective initiative.The innovation of Marx’s new worldview lies in its grasp of the essence of practice, which is a realistic, emotional, and active objective activity of human beings, and is the essence of social life. The Outline established Marx’s view of scientific practice, providing guidance for us to actively.